Frequency of Hyperprolactinemia in Infertile (Primary and Secondary) Women Presenting at OPD of Gyneacology - Moomal, .; Shaikh, Shahida (Biological and Clinical Sciences Research Journal, 2025)
Background: Infertility is a major reproductive health concern affecting up to 15% of couples globally. Among its multiple etiologies, endocrine abnormalities, particularly hyperprolactinemia, are recognized as frequent yet treatable causes of anovulation and menstrual irregularities. Objective: To determine the frequency of hyperprolactinemia among infertile women presenting to the gynecology outpatient department and to compare its occurrence between primary and secondary infertility. Methodology: This cross-sectional descriptive study was conducted at Shaikh Zaid women hospital Larkana from August 2023 to Jan 2024. A total of 135 infertile women aged 18–45 years were included using non-probability consecutive sampling. Women with thyroid or pituitary disorders, chronic illnesses, or recent use of dopamine-modulating drugs were excluded. After informed consent, demographic and clinical data were recorded, and fasting serum prolactin levels were measured using a chemiluminescent immunoassay. Results: The mean age of participants was 29.7 ± 5.1 years. Primary infertility was observed in 82 (60.7%) and secondary infertility in 53 (39.3%) women. Hyperprolactinemia was detected in 46 participants, yielding a frequency of 34.1%. The condition was significantly more prevalent in women with primary infertility (43.9%) compared to secondary infertility (18.9%) (p = 0.002). Mean serum prolactin levels were 32.4 ± 17.9 ng/mL in primary infertility and 20.6 ± 10.8 ng/mL in secondary infertility. Menstrual irregularities (95.6%) and galactorrhea (28.2%) were significantly more common among hyperprolactinemic women (p < 0.05). No significant association was found with age or BMI. Conclusion: Hyperprolactinemia is a prevalent and reversible cause of infertility, particularly among women with primary infertility.